Covid-19 omicron variant infection in neonates of Guangdong province-a report of 52 cases - Yang, Yi-Kang; Lin, Fen; Lin, Jian-Feng; Lin, Chun-Fan; Liu, Li-Li; Ma, Yu-Bin; Wang, Xian-Yao; Liao, Yu-Wei; Huang, Yu-Chan; Zeng, Guang-Kuan; Xiao, Bei-Ru; Huang, Shan-Hua; et al. (Frontiers in Pediatrics, 2023)
Abstract: Objective: To analyze the clinical characteristics of neonatal infection during the outbreak of COVID-19 omicron variant in Guangdong province of China. Method: The clinical data of neonates infected with COVID-19 omicron variant were collected from three hospitals of Guangdong province, their epidemiological history, clinical manifestation and prognosis were summarized. Results: From December 12, 2022 to January 15, 2023, a total of 52 neonates with COVID-19 infection were identified across three hospitals in Guangdong Province, including 34 males and 18 females. The age of diagnosis was 18.42± 6.32 days. 24 cases had clear contact history with adults who were suspected to be infected with COVID-19. The most common clinical manifestation was fever (43/52, 82.7%), the duration of fever was 1-8 days. The other clinical manifestations were cough (27/52, 51.9%), rales (21/52, 40.4%), nasal congestion (10/52, 19.2%), shortness of breath (2/52, 3.8%), and vomiting (4/52, 7.7%). C-reactive protein was only increased in 3 cases. Chest radiological examination was performed in 42 neonates, twenty-three cases showed abnormal chest radiographic findings, including ground-glass opacity and consolidation. Fifty cases were admitted with COVID-19 presentation, two cases were admitted for jaundice. The clinical classification included 3 cases of severe COVID-19 and one critical case. Fifty-one cases were cured and discharged after general treatment, and one critical case with respiratory failure was intubated and transferred to another hospital. The hospital stay was 6.59±2.77 days. Conclusion: The COVID-19 omicron variant infection in neonates is usually mild. The clinical manifestation and laboratory results are not specific, and the short-term prognosis is good.